(Ne)primernost uporabe kriterija avtohtonosti za urejanje položaja Romov v Sloveniji - Sancin, Vasilka (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2021)
The article discusses the legal protection of the rights of the Roma community and its members en- shrined in the existing international instruments and mechanisms, particularly those concerning the protection of minorities and human rights, and in the Slovenene legislation. It critically analyses the applicable legal sources, state practice and jurisprudence in order to prove the hypothesis that autochthony, as a criterion for recognising the special rights of the members of the Roma community in Slovenia, is not imbedded in the relevant international or Slovene law and is even incompatible with international legal obligations in the field of human rights. It criticizes the suggested amendments of the Roma Community Act, which are likely to result in a regression of the status of Roma community members in Slovenia and increased non-compliance with Slovenia’s international legal obligations.
Keywords: autochthony; avtohtonost; constitution; international legal protection of human rights; international legal protection of minorities; mednarodno pravo; Roma; Roma community; Roma Community Act; Romi; romska skupnost; ustava; varstvo človekovih pravic; varstvo manjšin; Zakon o romski skupnosti